An advanced irradiation facilities and its usage - 康兴伦 陈洪涛 江雪艳 宁劲松 于志刚 朱校斌 张卫国 (Chinese journal of oceanology and limnology, 2006)
A carrier type gamma irradiator is an advanced device currently installed in Qingdao Irradiation Center （QIC） and has been put into operation for nine years in Qingdao, China. It utilizes Co-60 as the radiation source; the initial Co-60 loading is 1.48×10^16Bq （0.4 million Curies）. Rubber, natural and synthetic polymers, heat-shrinkable films and tubes, disposable medical supplies, some foods and drugs have been irradiated for test in the past. Especially a great success achieved on the radiation of compound food for young shrimp. The practice demonstrates that the bacteria in the compound food can be destroyed by the irradiation at optimum dosage between 5 000--6 000 Gy.